Nonorganic sleep disorders and sleep quality among the general population of Mongolia - Enkhnaran Tumurbaatar; Gantsetseg Tumur-Ochir; Enkhjin Bat-Erdene; Tsogt-Itgel Munkhbat; Chimeddulam Erdenebaatar; Bulgantuya Bumandorj; Battuvshin Lkhagvasuren; Tsolmon Jadamba (Proceedings of the Mongolian Academy of Sciences)
The aim of this study was to determine the prevalence of non-organic sleep disorders and sleep quality, using a structured psychiatric interview following screening through the Pittsburgh Sleep Quality Index (PSQI) among the general population. This nationwide population-based cross-sectional study was carried out between August and October 2020 and involved 964 participants (74% women, mean age: 40.72±14.34) who were randomly selected from 64 clusters in 10 sites of Mongolia. 27.9% of the study participants were evaluated as having non-organic sleep disorders based on the diagnostic guidelines of the International Classification of Diseases, Tenth Edition, Clinical Modification (ICD-10). The prevalence of non-organic sleep disorders differed in age (p<0.001). Non-organic sleep disorders were related to age, employment, diastolic blood pressure, sleep quality, and quality of life. The prevalence of non-organic sleep disorders in the general population of Mongolia was calculated as 27.9%, while the prevalence rate of the poor sleep quality was 42.2%.